Predicted climate change effects on European perch (Perca fluviatilis L.) - A case study from the Curonian Lagoon, south-eastern Baltic. (31st May 2019) - Dainys, Justas; Jakubavičiūtė, Eglė; Gorfine, Harry; Pūtys, Žilvinas; Virbickas, Tomas; Jakimavičius, Darius; Šarauskienė, Diana; Meilutytė-Lukauskienė, Diana; Povilaitis, Arvydas; Bukantis, Arūnas; Kažys, Justas; Ložys, Linas
Abstract: Climate change is likely to increasingly impact estuarine fish populations. Changes in water temperature or salinity can have deleterious effects on fish growth and behaviour. A decrease in the abundance of freshwater fish in the northern areas of the Curonian Lagoon has been attributed to increased salinity of inflowing water from the Baltic Sea. Thus, this study investigated the effects of possible changes in environmental salinity and temperature on the growth and behaviour of perch ( Perca fluviatilis L.). Laboratory experiments revealed that brackish water (salinity 3 and 6) has neither a negative nor a positive effect on growth rates among perch young-of-the-year, when compared to freshwater (salinity 0). In contrast, results from behavioural experiments demonstrated that perch prefer to remain in brackish water (salinity 6) when given a choice between brackish and freshwater, and in warm water (18 °C) when given a choice between warm and cold water (12 °C). For this reason, the temperature rather than the salinity of inflowing colder brackish water from the Baltic Sea will be the most likely driver of short-term changes in fish distribution in the Curonian Lagoon. Highlights: Brackish water (salinity 3 and 6) has no effect on perch YOY growth rates. Perch prefer to remain in brackish (salinity 6) water compared to fresh (0) water. Perch prefer to remain in warm (18 °C) water compared cold (12 °C) water. Temperature is the driver of changes in fish distribution in the Curonian Lagoon.